PENDIDIKAN KARAKTER ISLAMI KELUARGA MUSTAHIK MELALUI PEMBERDAYAAN ZAKAT PRODUKTIF LAZISMU DI PURBOLINGGO LAMPUNG TIMUR - Wulan Nur Azizah; Heri Cahyono; Iswati Iswati (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
Mustahik families facing economic pressure have generally been unable to optimally carry out Islamic character education due to limited time, energy, and resources for guiding their children's moral development. This study aims to analyze Islamic character education practices within mustahik families receiving productive zakat and to identify the Islamic character values that develop through the Community Independent Livestock Program (Program Masyarakat Ternak Mandiri) at LAZISMU East Lampung. This study employed a qualitative approach with a case study design, collecting data through in-depth interviews, participatory observation, and documentation, with subjects purposively selected from mustahik families families enrolled in the LAZISMU East Lampung program. The findings indicate that the program indirectly contributes to Islamic character education through habituation, modeling, and experiential learning in facing challenges, with four character values identified: responsibility (amanah), patience (sabr), gratitude (shukr), and hard work and professionalism (itqan), although structured character education has not been consistently implemented as mustahik still prioritize the success of their livestock business which remains in a developing stage.